الفروق في مستوى الدافعية للإنـجاز بين التلاميذ المتفوقين والتلاميذ المتأخرين دراسيا - صرداوي, نزيم; عمور, ربيحة (جامعة الوادي University of Eloued, 2017)
هدفت هذه الدراسة إلى الكشف عن الفروق في الدافعية للإنجاز بين التلاميذ المتفوقين والمتأخرين دراسيا من السنة الثالثة ثانوي، وتكونت عينة الدراسة من (ن=200) تلميذ وتلميذة، بواقع 107 متأخر ومتأخرة دراسيا، و93 متفوقا ومتفوقة دراسيا. وتوصلت نتائج الدراسة الحالية عن عدم وجود فروق دالة إحصائيًا في مستوى الدافعية للإنجاز تعزى لمتغير مستوى التحصيل الدراسي، كما أسفرت عن عدم وجود فروق دالة إحصائيًا في مستوى الدافعية للإنجاز تعزى لمتغير الجنس. This study aims to detect the differences in achievement motivation between overachievers and underachievers students of third year secondary school. The sample consisted of (200) male and female students. It was divided into two groups: (93) overachievers and (107) underachievers. The results indicated that there are no statistically significant differences in achievement motivation between the overachievers and underachievers. In addition, there are no statistically significant differences in achievement motivation due to gender variable.
من السنة الثالثة ثانوي
مقال
Keywords: الدافعية للإنجاز؛ المتفوقين دراسيا؛ المتأخرين دراسيا؛ تلاميذ السنة الثالثة ثانوي; achievement motivation, overachiever and underachiever students, third year secondary school students